Auditoria de cumplimiento en relación con las obligaciones tributarias a la empresa Costello Sport Music Bar cantón Quevedo año 2013 - Poma Sánchez, Edison Rene (2015)
"Costello Sport Music Bar" located in Street Pier, Avenue Eloy Alfaro, Quarter Intersection and Fifth, Low Building Palacio of Glass, being a forced society of taking accounting is subject to fulfill each one of the Tributary obligations, as the SRI it indicates it in the RUC. Also, Costello and as many company youths, it usually makes errors during the process of the tributary execution, being this way, the audit has applied it to him with the objective of analyzing the execution of the Obligations settled down by the tributary administration, to examine the mechanisms of internal control to minimize the error margin in the accounting of the tributary items. To evaluate the main conciliatory departures from the tax to the rent, and the accounting procedures and finally to elaborate the report of tributary execution for the taking of decisions. This audit required of visit preliminary, he/she interviews, surveys and questionnaire, with a scientific, applied investigation, bibliographical to have better understanding of the development of the Tributary work, and of internal control. It has also been planned and programmed, to carry out in a more organized way the execution of the work papers, considering each one of the obligations that the company should complete as society. By means of evaluations, physical revisions, reconciliations, analysis, and observance of the dispositions settled down by the tributary administration. Being able to detect through them strengths and weaknesses. Strengths during the development of the declarations in Annexed Shareholders, Participate, Partners, Members of Directory and Administrating, Annexed Relationship of Dependence, Retentions in the Source the Tax to the Rent, as taking an appropriate registration of the same one, to conserve properly in files the invoices that it sustains the countable registration. And weaknesses in the Imposed declaration to the Added Value, as the non presentation of all the revenues perceived in the month of October of $2263.57 that you/they also harm the main conciliatory departures from the tax to the rent. And weaknesses in their Internal Controls with 12% of watering level to have personal little trained, to have errors in the process accountants and to ignore the normative one tributary